Problematika Lembaga Manajemen Kolektif Nasional (LMKN) Dalam Menghimpun Royalti Hak Cipta Di Indonesia - Yoyo Arifardhani (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2022)
Indonesia is an archipelagic country with a diverse range of arts, cultures, ethnicity, and religions that must be considered and protected as national assets. Copyright is one of the world’s most extensive intellectual property rights and involves a large number of people. According to Article 4 of Copyright Law No. 28 of 2014, a creator has the exclusive right to reproduce and distribute his work to third parties. Furthermore, the concept of economic rights, which is related to copyright, is defined as the right to benefit economically from the creation. According to Article 1 Paragraph 21 of the Copyright Law, royalties are defined as a reward for the use of the economic rights of a particular work or related rights products received by the creator or the owner of the related rights. Consequently, an institution known as the National Collective Management Organization (LMKN) was formed to implement the license to announce songs and music in Indonesia and also had the authority to draw, collect, and distribute royalties for commercial users. This study examined the role of LMKN in the collection of royalties in copyright and how the LMKN regulation in Government Regulation No. 56 of 2021 concerning the Management of Royalties for Song and Music Copyrights can guarantee the fulfilment of the creator’s economic rights. Lastly, an empirical juridical legal research method was used to address these issues.Keywords: Authority; LMKN; Government Regulation; Royalties. AbstrakIndonesia merupakan negara kepulauan dengan keragaman seni, budaya, suku, dan agama yang harus diperhatikan dan dilindungi sebagai aset nasional. Hak cipta adalah salah satu hak kekayaan intelektual paling luas di dunia dan melibatkan banyak orang. Menurut Pasal 4 Undang-Undang Hak Cipta No. 28 Tahun 2014, pencipta memiliki hak eksklusif untuk memperbanyak dan mendistribusikan ciptaannya kepada pihak ketiga. Selanjutnya konsep hak ekonomi yang berkaitan dengan hak cipta diartikan sebagai hak untuk memperoleh manfaat secara ekonomis dari ciptaan. Menurut Pasal 1 Ayat 21 Undang-Undang Hak Cipta, royalti didefinisikan sebagai imbalan atas penggunaan hak ekonomis suatu ciptaan atau produk hak terkait yang diterima oleh pencipta atau pemilik hak terkait. Oleh karena itu, dibentuklah lembaga yang bernama Lembaga Manajemen Kolektif Nasional (LMKN) untuk melaksanakan izin mengumumkan lagu dan musik di Indonesia serta berwenang untuk menarik, memungut, dan mendistribusikan royalti bagi pengguna komersial. Penelitian ini mengkaji tentang peran LMKN dalam pemungutan royalti pada hak cipta dan bagaimana pengaturan LMKN dalam Peraturan Pemerintah Nomor 56 Tahun 2021 tentang Pengelolaan Royalti Hak Cipta Lagu dan Musik dapat menjamin pemenuhan hak ekonomi pencipta. Terakhir, metode penelitian hukum yuridis empiris digunakan untuk mengatasi masalah ini.Kata Kunci: Wewenang; LMKN; Peraturan Pemerintah; Royalti.